2020
DOI: 10.3390/su12083410
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cloud Service Provider Development by a Z-Number-Based DNMA Method with Gini-Coefficient-Based Weight Determination

Abstract: The sustainable development of cloud service providers (CSPs) is a significant multiple criteria decision making (MCDM) problem, involving the intrinsic relations among multiple alternatives, (quantitative and qualitative) decision criteria and decision-experts for the selection of trustworthy CSPs. Most existing MCDM methods for CSP selection incorporated only one normalization technique in benefit and cost criteria, which would mislead the decision results and limit the applications of these methods. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…A summary of the reviewed papers related to SDG 9 issues [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] is presented in Table 8. In most articles concerning SDG 9, MCDM approaches were applied to evaluate the industry's sustainability performance in national contexts to overcome barriers to achieve this SDG [80,81,84,85,87,89].…”
Section: Sdg 9: Industry Innovation and Infrastructurementioning
confidence: 99%
See 3 more Smart Citations
“…A summary of the reviewed papers related to SDG 9 issues [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] is presented in Table 8. In most articles concerning SDG 9, MCDM approaches were applied to evaluate the industry's sustainability performance in national contexts to overcome barriers to achieve this SDG [80,81,84,85,87,89].…”
Section: Sdg 9: Industry Innovation and Infrastructurementioning
confidence: 99%
“…Their evaluation showed that the proposed mixed strategy portfolio for green aviation fleet management could be determined using limited resources. Some authors concentrated their efforts on selecting or ranking strategies to make the infrastructure sector more sustainable [81,87,[89][90][91][92][93][94].…”
Section: Sdg 9: Industry Innovation and Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Al‐Faifi et al 45 presented a hybrid model with clustering and MCDM for the appropriate selection of CVs based on smart data from a simulation in MATLAB. Lai et al 46 proposed an integrated model with Z ‐numbers to select suitable sustainable CVs with Gini index and double normalized‐based multiple aggregation methods. Hussain et al 47 presented a novel framework for CV selection under the SaaS category by extending the best–worst (BW) method to fuzzy context.…”
Section: Introductionmentioning
confidence: 99%